A smart monitor and data analysis system for playground safety - Leong, She Teng (2019)
Playground safety is a safety concern for many parents. With the rising popularity of indoor playgrounds, it is important to ensure the safety of the children while they are there. The current monitoring systems used mainly comprise smart watches which can be quite costly to design and implement. Following the trend of digitization and Internet of Things (IoT), this project would be implementing a low cost monitoring system that can potentially reduce accident rates. The main aim of this project is to prevent accidents through a quick and simple phone notification upon sensor detection. Various sensors were considered and ultimately, RFID sensors with antenna coupled with passive wrist tags was used. Sensors could be placed at areas with high accident risks, upon detection, the parents would be notified on their phones via the Telegram messaging mobile application on the location of their children. This gives parents an opportunity to reach their children before an accident occurs. Additionally, a website that records all the sensor detection for each tags is available for parents to access and keep a record of their child’s movement. To reduce the complexity on the user end, Amazon Web Services was selected to implement the software components of this project from receiving sensor information, updating of database and ultimately, updating web application as well as sending notifications to parents.